2017
DOI: 10.2147/cmar.s142324
|View full text |Cite
|
Sign up to set email alerts
|

High expression of eIF3d is associated with poor prognosis in patients with gastric cancer

Abstract: BackgroundEukaryotic initiation factor 3 subunit d (eIF3d) is the largest subunit of eIF3, which is shown to promote protein synthesis in cancer cells. Increased expression of eIF3d has been shown in some types of cancers, but has not been previously studied in gastric cancer (GC). Thus, the aim of this study was to analyze eIF3d expression in GC.Patients and methodsExpression of eIF3d was detected by immunohistochemistry in GC tissues and adjacent noncancerous (ANC) tissues. Samples were obtained from 210 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
4
10
0
Order By: Relevance
“…We then sought to determine whether eIF3d affects the function of CD8+ T cells. Previous studies on eIF3d in tumours have shown that over expression leads to the abnormal proliferation of tumour cells [35, 41, 43]. Our study demonstrated that a reduction in eIF3d expression in human CD8+ T cells attenuated cell proliferation and secretion of IFN-γ and promoted apoptosis, which was consistent with the finding of the function of this protein in tumour cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We then sought to determine whether eIF3d affects the function of CD8+ T cells. Previous studies on eIF3d in tumours have shown that over expression leads to the abnormal proliferation of tumour cells [35, 41, 43]. Our study demonstrated that a reduction in eIF3d expression in human CD8+ T cells attenuated cell proliferation and secretion of IFN-γ and promoted apoptosis, which was consistent with the finding of the function of this protein in tumour cells.…”
Section: Discussionsupporting
confidence: 91%
“…We first systematically analysed the expression levels of 13 eIF3 subunit mRNAs in EHI and HCs and found that expression of eIF3d mRNA was lowest in the RP group and significantly negatively correlated with disease progression. Previous reports have indicated that eIF3d can serve as a marker for tumour metastasis and prognosis [24, 41, 42]. Our study suggests that in EHI, a low level of eIF3d in the host is correlated with rapid disease progression.…”
Section: Discussionsupporting
confidence: 66%
“…The overexpression of eIF3D has been observed to promote cell proliferation, migration, or/and tumour growth in several cancer entities, including ovarian cancer [31], renal cell carcinoma [32], gastric cancer (GC) [33], and gallbladder cancer (GBC) [34]. As being discovered in our study, all these high levels of eIF3D are associated with advanced tumour stage, indicating its potential role in tumour development.…”
Section: Discussionsupporting
confidence: 70%
“…The majority of GC patients are diagnosed at an advanced stage and receive a poor prognosis (20). One of the reasons for the poor outcomes of GC is the malignant biological behaviors of GC cells, particularly for those with low-to-intermediate differentiation stages, which often possess strong abilities in proliferation, migration, invasion and tumorigenesis (21,22).…”
Section: Discussionmentioning
confidence: 99%